Public Health Nurses' Professional Practices to Prevent, Recognize, and Respond to Suspected Child Maltreatment in Home Visiting: An Interpretive Descriptive Study - Susan M. Jack; Andrea Gonzalez; Lenora Marcellus; Lil Tonmyr; Colleen Varcoe; Natasha Van Borek; Debbie Sheehan; Karen MacKinnon; Karen Campbell; Nicole Catherine; Christine Kurtz Landy; Harriet L. MacMillan; et al. (SAGE Publishing, 2021)
The purpose of this analysis was to understand public health nurses' experiences in preventing and addressing suspected child maltreatment within the context of home visiting. The principles of interpretive description guided study decisions and data were generated from interviews with 47 public health nurses. Data were analyzed using reflexive thematic analysis. The findings highlighted that public health nurses have an important role in the primary prevention of child maltreatment. These nurses described a six-step process for managing their duty to report suspected child maltreatment within the context of nurse-client relationships. When indicators of suspected child maltreatment were present, examination of experiential practice revealed that nurses developed reporting processes that maximized child safety, highlighted maternal strengths, and created opportunities to maintain the nurse-client relationship. Even with child protection involvement, public health nurses have a central role in continuing to work with families to develop safe and competent parenting skills.